Experimental Analysis for Factors Affecting the Repeatability of Plastics Injection Molding Tests on the Self-developed Apparatus - Yugang Huang; Duxin Li; Yuejun Liu (International Journal of Science and Engineering, 2013)
To improve the repeatability of the injection molding test result, the affecting factors were investigated by means of experiments. Besides the traditional processing parameter, the factors of test conditions were also considered. In order to focus on the molding process rather than the molded part, the curve measurement of the melt pressure at the entrance to the nozzle was used as the output characteristic. Experiments for polypropylene (PP) showed that the injected volume was the key processing parameter. Within the test conditions, the injection number is the most important factor. According to the analysis the operating procedure was improved effectively. Doi: 10.12777/ijse.5.1.6-11 [How to cite this article: Huang, Y., Li, D., Liu, Y. (2013). Experimental Analysis for Factors Affecting the Repeatability of Plastics Injection Molding Tests on the Self-developed Apparatus. International Journal of Science and Engineering, 5(1),6-11. Doi: 10.12777/ijse.5.1.6-11]